The bonds of humanity : Cicero's legacies in European social and political thought, ca. 1100-ca. 1550 - Nederman, Cary J. (The Pennsylvania State University Press, 2020)
"Surveys the many different impacts of Ciceronian theories on a diverse array of texts and authors between 1100 and 1550, presenting a counternarrative to the widely accepted belief in the dominance of Aristotelianism in early European political and social thought"-- Provided by publisher.
Keywords: Cicero, Marcus Tullius -- Influence.; Cicero, Marcus Tullius; Ciceronianism.; Social sciences -- Europe -- History.; Political science -- Europe -- History.; Cicéronianisme.; Sciences sociales -- Europe -- Histoire.; HISTORY / Medieval; Ciceronianism; Influence (Literary, artistic, etc.); Political science; Social sciences; Europe; Electronic books.; History